Bluetongue virus: the role of synchrotron radiation - Diprose, J; Grimes, J; Gouet, P; Malby, R; Burroughs, J; Lescar, J; Rassmussen, B; Mertens, P; Stuart, D (1999)
The determination of the structure of the transcriptionally active core particle of bluetongue virus is discussed. This particle is approximately 700 Å in diameter and reasonably well ordered, but fragile, crystals have been obtained from two different serotypes of the virus. Cryocrystallography proved difficult and a large number of crystals were analysed at room temperature to accumulate a reasonably complete data set. The effects of synchrotron optics, station design and detector on the signal-to-noise for these weak data are discussed, with particular reference to station ID2 at the European Synchrotron Radiation Facility. Once the data had been gathered, structure determination was straightforward, using a model derived from a combination of electron microscopy and protein crystallography to obtain initial phases. Despite apparent isomorphism, it is suspected that the crystal lattice 'ages', perhaps reflecting both the inevitable weakness of the forces holding crystals of such a large macromolecular complex together and flexibility in the particle.